Strength and conditioning professional burnout: Warning signs, prevention, and recovery - Snarr, R. L.; Elias, C. M.; Eckert, R. M.; Williams, T.; Casey, J. C. (Journal of Australian Strength and Conditioning, 2017)
Burnout is a multidimensional, psychological syndrome, characterized by chronic physical and emotional exhaustion, feelings of reduced accomplishment, and feelings of disengagement from a previously enjoyed profession or activity. While much of the literature on burnout involves health care providers, little information is available regarding burnout in strength and conditioning professionals. However, due to the competitive and high pressure nature of strength and conditioning, it is not uncommon for individuals to experience burnout. Therefore, it is important that strength and conditioning professionals be able to identify warning signs of burnout, which may manifest themselves as cognitive, affective, physical, behavioral, or emotional symptoms. Preventive as well as recovery strategies have been documented in other health care professions as being effective, however, these strategies will need to be empirically validated in strength and conditioning professionals. Future research is needed in order to identify and validate burnout prevention and recovery strategies for the strength and conditioning profession.